Granulocytic Sarcoma Presenting as a Palpable Breast Lump - Fernandes Vieira, Victor; Vo, Quoc Duy; Bouquet de la Jolinière, Jean; Khomsi, Fathi; Feki, Anis; Hoogewoud, Henri-Marcel (Frontiers in Surgery, 2017)
ABSTRACT: We report the case of a 45-year-old woman who palpated a voluminous painless lump in the superior outer quadrant of her left breast. Her past medical history revealed an acute myeloid leukemia treated and considered in remission 1 month prior to this discovery. Imaging work-up by mammogram, US and MRI showed multiples masses suspect of malignancy in both breasts. US-guided needle biopsy was performed in the palpable mass and in one of the multiple lesions located in the right breast. Histologic findings were compatible with a granulocytic sarcoma in both breasts which was considered as a relapse of the acute myeloid leukemia treated a few months earlier.